Characteristics of diffuse hemispheric gliomas, H3 G34-mutant in adults - Picart, Thiébaud; Barritault, Marc; Poncet, Delphine; Berner, Lise-Prune; Izquierdo, Cristina; Tabouret, Emeline; Figarella-Branger, Dominique; Idbaïh, Ahmed; Bielle, Franck; Bourg, Véronique; Vandenbos, Fanny Burel; Moyal, Elizabeth Cohen-Jonathan; et al. (Neuro-oncology advances, 2021)
Abstract Background Diffuse hemispheric gliomas, H3 G34-mutant (DHG H3G34-mutant) constitute a distinct type of aggressive brain tumors. Although initially described in children, they can also affect adults. The aims of this study were to describe the characteristics of DHG H3G34-mutant in adults and to compare them to those of established types of adult WHO grade IV gliomas. Methods The characteristics of 17 adult DHG H3G34-mutant, 32 H3.3 K27M-mutant diffuse midline gliomas (DMG), 100 IDH-wildtype, and 36 IDH-mutant glioblastomas were retrospectively analyzed. Results Median age at diagnosis in adult DHG H3G34-mutant was 25 years (range: 19–33). All tumors were hemispheric. For 9 patients (56%), absent or faint contrast enhancement initially suggested another diagnosis than a high-grade glioma, and diffusion-weighted imaging seemed retrospectively more helpful to suspect an aggressive tumor than MR-spectroscopy and perfusion MRI. All cases were IDH-wildtype. Most cases were immunonegative for ATRX (93%) and Olig2 (100%) and exhibited MGMT promoter methylation (82%). The clinical and radiological presentations of adult DHG H3G34-mutant were different from those of established types of adult grade IV gliomas. Median overall survival of adult DHG H3G34-mutant was 12.4 months compared to 19.6 months (P = .56), 11.7 months (P = .45), and 50.5 months (P = .006) in H3.3 K27M-mutant DMG, IDH-wildtype, and IDH-mutant glioblastomas, respectively. Conclusions Adult DHG H3G34-mutant are associated with distinct characteristics compared to those of established types of adult WHO grade IV gliomas. This study supports considering these tumors as a new type of WHO grade IV glioma in future classifications.